2021
DOI: 10.1002/chem.202102672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Defects on LaNiO3 Perovskite Electrocatalysts for the Oxygen Evolution Reaction

Abstract: Perovskite oxides are regarded as promising electrocatalysts for water splitting due to their cost‐effectiveness, high efficiency and durability in the oxygen evolution reaction (OER). Despite these advantages, a fundamental understanding of how critical structural parameters of perovskite electrocatalysts influence their activity and stability is lacking. Here, we investigate the impact of structural defects on OER performance for representative LaNiO3 perovskite electrocatalysts. Hydrogen reduction of 700 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 46 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…In contrast, η 10 increased to 322 mV (Ag/LNO-0.3) and 343 mV (Ag/LNO-0.5) as x increased to 0.3 and 0.5, respectively. The trend in the OER performance of Ag/LNO- x electrocatalysts was not correlated with the amount of the additional NiO phase in the Ag/LNO- x , and a recent report also showed that NiO exhibited a much higher overpotential for OER compared to the pristine LNO . Therefore, the existence of NiO was not considered for analyzing the improvement of the OER performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, η 10 increased to 322 mV (Ag/LNO-0.3) and 343 mV (Ag/LNO-0.5) as x increased to 0.3 and 0.5, respectively. The trend in the OER performance of Ag/LNO- x electrocatalysts was not correlated with the amount of the additional NiO phase in the Ag/LNO- x , and a recent report also showed that NiO exhibited a much higher overpotential for OER compared to the pristine LNO . Therefore, the existence of NiO was not considered for analyzing the improvement of the OER performance.…”
Section: Resultsmentioning
confidence: 99%
“…The trend in the OER performance of Ag/LNO-x electrocatalysts was not correlated with the amount of the additional NiO phase in the Ag/LNO-x, and a recent report also showed that NiO exhibited a much higher overpotential for OER compared to the pristine LNO. 55 Therefore, the existence of NiO was not considered for analyzing the improvement of the OER performance. The activity comparison of the Ag/LNO-x electrocatalysts suggested that an appropriate amount of Ag nanoparticles would enhance the OER electrocatalytic activity through the synergetic effect between Ag nanoparticles and the LNO surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, ternary metal oxides such as ABO 3 (perovskite) 63 and AB 2 O 4 (spinel) [93][94][95] show better catalytic activity than binary metal oxides. This is due to the coexistence of multiple valences of metal cations causing intervalence charge transfer (IVCT), 118,119 and/or the formation of oxygen vacancies and structural defects in the system, 29,120,121 and these play an essential role in improving the catalytic efficiency. Detailed information on perovskite and spinel type materials and their electrochemical performances are summarised in Table 3.…”
Section: Perovskite (Abo 3 ) and Spinel Oxides (Ab 2 O 4 )mentioning
confidence: 99%
“…Shifting the d-band center by creating defects or improving vacancies is an effective way to regulate electronic and geometric structures because downshifting can aid the active intermediate desorption of active intermediates and upshifting promotes the adsorption of the active intermediates [ 89 , 90 , 91 , 92 ], leading to an enhancement in the reactivity of active sites, which significantly facilitates the activity of electrocatalytic water splitting.…”
Section: Strategies For Tuning the D-band Center Of Materials Based O...mentioning
confidence: 99%